2004
DOI: 10.1111/j.1365-313x.2004.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid dependent signaling promotes basal thermotolerance but is not essential for acquired thermotolerance in Arabidopsis thaliana

Abstract: SummarySalicylic acid (SA) is reported to protect plants from heat shock (HS), but insuf®cient is known about its role in thermotolerance or how this relates to SA signaling in pathogen resistance. We tested thermotolerance and expression of pathogenesis-related (PR) and HS proteins (HSPs) in Arabidopsis thaliana genotypes with modi®ed SA signaling: plants with the SA hydroxylase NahG transgene, the nonexpresser of PR proteins (npr1) mutant, and the constitutive expressers of PR proteins (cpr1 and cpr5) mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
244
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(264 citation statements)
references
References 78 publications
10
244
0
10
Order By: Relevance
“…HS was found to induce SA-regulated pathogenesis-related 1 (PR1) transcripts, and the constitutive expression of PR1 protein mutant (cpr1-5) exhibited an enhanced thermotolerant phenotype (Clarke et al, 2004;. This indicates that SA and PR1, originally defined as being involved in antipathogenic responses, can also promote heat tolerance in A. thaliana.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…HS was found to induce SA-regulated pathogenesis-related 1 (PR1) transcripts, and the constitutive expression of PR1 protein mutant (cpr1-5) exhibited an enhanced thermotolerant phenotype (Clarke et al, 2004;. This indicates that SA and PR1, originally defined as being involved in antipathogenic responses, can also promote heat tolerance in A. thaliana.…”
Section: Introductionmentioning
confidence: 94%
“…Electrolyte leakage measurements Measurement of leaf electrolyte leakage (EL) was carried out essentially as described by Clarke et al (2004). For experiments where EL was measured during heat treatment at 42°C, the aerial parts of 3-week-old plants were placed into glass tubes containing 5 ml of water and incubated in a waterbath at 42°C in the dark.…”
Section: Heat Stress Treatmentsmentioning
confidence: 99%
“…Previous studies have shown that heat shock transcription factors (HSFs) 2 play an important role in thermotolerance in plants and other organisms, regulating heat shock proteins (HSPs) as well as different acclimation and detoxification proteins (7)(8)(9)(10). In contrast, although several other pathways, involving ethylene, salicylic acid (SA), and trehalose, have recently been proposed to play an important role in thermotolerance in plants (5,(11)(12)(13)(14)(15), a key regulator of these responses was not identified.…”
mentioning
confidence: 99%
“…Over the past few years, a more general role for SA as a mediator of diverse stress responses has been emerging. For example, in Arabidopsis SA is synthesized in response to abiotic stresses such as UV-C (30), ozone (31), cold (32), and heat (33,34) and has been shown to play a role in stress-induced developmental transitions, including flowering (35) and senescence (36). Although AtICS1 has been confirmed to be involved in many of these processes, it has only been implicated in others, such as cold-tolerant growth.…”
mentioning
confidence: 99%